2021
DOI: 10.1186/s12885-021-08972-5
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide sensitivity of malignant glioma cell lines – a systematic review assessing consistencies between in vitro studies

Abstract: Background Malignant glioma cell line models are integral to pre-clinical testing of novel potential therapies. Accurate prediction of likely efficacy in the clinic requires that these models are reliable and consistent. We assessed this by examining the reporting of experimental conditions and sensitivity to temozolomide in glioma cells lines. Methods We searched Medline and Embase (Jan 1994-Jan 2021) for studies evaluating the effect of temozolom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 30 publications
4
19
0
Order By: Relevance
“…A recent study has also identified suboptimal reporting of basic experimental parameters and varying cell viability reducing effects of TMZ in in vitro glioma cell line experiments with TMZ single treatment. 14 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent study has also identified suboptimal reporting of basic experimental parameters and varying cell viability reducing effects of TMZ in in vitro glioma cell line experiments with TMZ single treatment. 14 …”
Section: Discussionmentioning
confidence: 99%
“…However, the reporting of experimental parameters in this literature—including such fundamental issues as the concentration of the drug and the treatment duration—is limited. A recent study has also identified suboptimal reporting of basic experimental parameters and varying cell viability reducing effects of TMZ in in vitro glioma cell line experiments with TMZ single treatment 14…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations